Mental Health Care Provider's Perspectives Toward Adopting a Novel Technology to Improve Medication Adherence. Issue 2 (7th April 2022) - Liberman, Joshua N.; Davis, Tigwa; Velligan, Dawn; Robinson, Delbert; Carpenter, William; Jaeger, Chris; Waters, Heidi; Ruetsch, Charles; Forma, Felicia
Abstract : Objective: To understand perspectives of mental health care providers regarding barriers and drivers of adopting a medication ingestible event monitoring (IEM) system in clinical practice. Methods: Between April and October 2019, a cross‐sectional, online survey was conducted among 131 prescribing clinicians and 119 non‐prescribing clinicians providing care to patients with major depressive disorder, bipolar disorder, and schizophrenia. Results: Most prescribing clinicians were physicians (79.4%) while most non‐prescribing clinicians (52.9%) were licensed clinical social workers, followed by counselors (30.8%), clinical psychologists (13.4%), and case managers (2.5%). Most respondents (93.2%) reported that clinicians can influence adherence, that the IEM technology was in their patients' best interest (63.6%), and a willingness to beta test the technology (54.8%). Support was positively associated with prescribing clinicians (OR: 2.2; 95% CI: 1.1, 4.5), belief that antipsychotics reduce the health, social, or financial consequences of the condition (OR: 3.8; 95% CI: 1.3, 11.0), concern for patients' well‐being without monitoring (OR: 3.3; 95% CI: 1.2, 8.7), and belief the technology will enhance clinical alliance (OR: 3.1; 95% CI: 1.5, 6.3) or improve patient engagement (OR: 3.0; 95% CI: 1.5, 6.2). Support was inversely related to concerns about appropriate follow‐up actions (OR: 0.4; 95% CI: 0.2, 0.9) and responsibilities (OR: 0.3; 95% CI: 0.1, 0.8) when using the technology. Conclusions: Our results suggest that IEM sensor technology adoption will depend upon additional evidence that patients will actively engage in the use of the technology, will benefit from the technology through improved outcomes, and that the additional burden placed upon providers is minimal compared to the potential benefit. Key Points: Among clinicians with prescribing authority, 91.6% are concerned about the quality of self‐reported medication adherence and 75.6% reported that the IEM sensor technology would be in their patients' "best interest". Most prescribing (85.5%) and non‐prescribing (74.0%) clinicians believe that the IEM sensor technology will either improve patient outcomes or practice efficiency. A key barrier to adoption appears to be concern about how to incorporate these data into practice.